Kidney Disease Management in the Hospital Setting: A Focus on Inappropriate Drug Prescriptions in Older Patients - Arcoraci, Vincenzo; Barbieri, Maria Antonietta; Rottura, Michelangelo; Nobili, Alessandro; Natoli, Giuseppe; Argano, Christiano; Squadrito, Giovanni; Squadrito, Francesco; Corrao, Salvatore; , on behalf of the REPOSI investigators (Frontiers in Pharmacology, 2021)
Aging with multimorbidity and polytherapy are the most significant factors that could led to inappropriate prescribing of contraindicated medications in patients with chronic kidney disease (CKD). The aim of this study was to evaluate the prescriptions of contraindicated drugs in older adults in CKD and to identify their associated factors in a hospital context. An observational retrospective study was carried out considering all patients ≥65 years with at least one serum creatinine value recorded into the REPOSI register into 2010–2016 period. The estimated glomerular filtration rate (eGFR) was applied to identify CKD. A descriptive analysis was performed to compare demographic and clinical characteristics; logistic regression models were used to estimate factors of inappropriate and percentage changes of drug use during hospitalization. A total of 4,713 hospitalized patients were recorded, of which 49.8% had an eGFR <60 ml/min/1.73 m2; the 21.9% were in treatment with at least one inappropriate drug at the time of hospital admission with a decrease of 3.0% at discharge (p = 0.010). The probability of using at least one contraindicated drug was significantly higher in patients treated with more several drugs (OR 1.21, 95% CI 1.16–1.25, p <0.001) and with CKD end-stages (G4: 16.90, 11.38–25.12, p < 0.001; G5: 19.38, 11.51–32.64, p < 0.001). Low-dose acetylsalicylic acid was the contraindicated drug mainly used at the time of admission, reducing 1.2% at discharge. An overall increase in therapeutic appropriateness in hospitalized older patients with CKD was observed, despite a small percentage of therapeutic inappropriateness at discharge that underlines the need for a closer collaboration with the pharmacologist to improve the drug management.